Surgical Management of Acute Presentation and Outcome of Patients With Complicated Abdominal Tuberculosis - Sadia jaskani ,Nadir Mehmood , Nazim M Khan , Hina Dilruba Khan ,Idrees M Anwar (Journal of Rawalpindi Medical College, 2016)
Background: To study the acute presentation, surgical management and outcome of patients with abdominal tuberculosis. Method: All adult patients of either gender with clinical diagnosis of abdominal tuberculosis were included in this descriptive study. All admitted cases were assessed by history, physical examination and relevant investigations. Patients with signs of peritonitis were operated in emergency after resuscitation. Pre and postoperatively, all patients were treated with anti-tuberculous drugs. Results: Out of 161 adult patients with abdominal tuberculosis, 40.4% patients were males and 59.6% females with a male to female ratio of 1: 1.47. The mean age was 35.9 years and majority (72.7%) belonged to poor families. 54.7% patients presented with features of peritonitis and 43.5% with acute and sub-acute intestinal obstruction. Majority(88.2%) required surgical intervention and most common preoperative finding was intestinal perforation peritonitis (50.3%). Ileostomy was the most frequently performed procedure (54.2%) and only 2.1% patients underwent primary anastomosis. Eighty nine(55.3%) patients were discharged and 72 (44.7%) expired. Conclusion: Majority were young females, belonging to poor families. Most patients had primary abdominal tuberculosis and presented with complications like acute intestinal obstruction and intestinal perforation peritonitis, requiring emergency laparotomy. Gut exteriorization was the commonest surgical intervention. Primary anastomosis was not performed because of the poor nutritional status and diseased condition of the gut.A high mortality rate was encountered due to late presentation of the disease resulting in development of complications like perforation peritonitis.